2011
DOI: 10.1177/1744987111414535
|View full text |Cite
|
Sign up to set email alerts
|

‘You’ve got to keep account of heads all the time’: staff perceptions of caring for people with dementia

Abstract: Research Aim: Little is known regarding the pressures of working within dementia care units as the majority of literature has focused broadly on long-term care (LTC) rather than the provision of specialised dementia care. This study aimed to explore the perceptions of staff in relation to their capacity to manage behaviour and care needs of people with dementia living within the dementia-specific environment. Individual interviews were conducted with 35 care staff from three dementia care units in Brisbane, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Participating staff adopted a task‐oriented approach to care and task completion overrode their desire for development of therapeutic relationships. This finding is supported by other research that found that the psychosocial or emotional needs of clients are not acknowledged or allowed to hinder staff members' ability to complete their allocated tasks . However, relationships between older people, staff and families can evolve over time if staff are educated and trained to work within a relationship‐centred model.…”
Section: Discussionmentioning
confidence: 61%
“…Participating staff adopted a task‐oriented approach to care and task completion overrode their desire for development of therapeutic relationships. This finding is supported by other research that found that the psychosocial or emotional needs of clients are not acknowledged or allowed to hinder staff members' ability to complete their allocated tasks . However, relationships between older people, staff and families can evolve over time if staff are educated and trained to work within a relationship‐centred model.…”
Section: Discussionmentioning
confidence: 61%
“…The full findings of the interviews are reported in the original published paper that examined care staff's perceived ability to manage and care for older people living in dementiaspecific facilities [12]. The findings reported within the published paper identified that the majority of the care staff not only acknowledged but also were firmly committed to the importance of dementia education and training, particularly in the management of common challenging behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Audio-taped recordings of the interviews were deleted once verbatim transcription of all interviews was completed. As outlined in the original published paper [12], interview data were analysed using an interpretive approach.…”
Section: Methodsmentioning
confidence: 99%
“…Care provided by frontline staff is generally underappreciated and their perceptions of quality of care are often overlooked (Chung, 2013;Lee, Chaudhury, & Hung, 2014;Stockwell-Smith, Jones, & Moyle, 2011). Direct engagement of the nursing and kitchen staff provides a more focused approach to investigate the complexity of mealtime practice.…”
Section: Discussionmentioning
confidence: 99%